Design and application of weight-on-bit control system for drilling process: A variable-gain integrated controller with multiple-model parameter estimation. (January 2023) - Ma, Sike; Wu, Min; Chen, Luefeng; Lu, Chengda
Abstract: Controlling weight-on-bit is essential in the drilling process, which determines the rock-breaking performance, drill bit wear, and wellbore quality. This paper aims to develop a weight-on-bit control system for field implementation, using a variable-gain integrated controller and a multiple-model parameter estimator. First, a weight-on-bit dynamic model for controller synthesis is derived according to the real drilling scenario. Then, the integrated controller is designed with two parts: a variable-gain proportional–integral controller and a dynamic output feedback controller, which separates the design of the system's high-order from low-order parts. The controller gain is tuned through a multiple-model parameter estimator, which estimates uncertain parameters related to rock strength. The established control system is implemented in a typical electrical drilling rig. It meets the requirement of adapting to different formations, considering the flexible drill string and the variable feed motor speed threshold. Numerical and field application results confirm the effectiveness of the developed system.